Dirt roads to justice and heartland girls: coercive sexual environments in non-metropolitan communities - Terry, April Nicole (Kansas State University, 2018)
This study analyzes in-depth interviews with incarcerated girls and young women, as well as contributions from community actors, to assess coercive sexual environments (CSE) in non-urban areas. CSEs represent an area of limited research that spotlights spatial disadvantage and sexual exploitation of at-risk girls, generating long-lasting negative effects for young women such as sexual harassment, exploitation, and sexual violence. Little is known about how CSEs may increase risk for girls’ involvement in the criminal justice system; further, all previous CSE research has been conducted in urban areas. To address these voids, the current study takes place in a primarily rural state, representing social control mechanisms somewhat different from cityscapes. Using a multi-pronged conceptual model of gendered pathways, ecological factors, and feminist criminology, the project relies heavily on stories from incarcerated girls and women. It identifies gender-specific mechanisms that perpetuate disadvantage and violence, examining how such apparatus may create a pipeline into the justice system. Tracing participants’ community roots, the study further gathers structural and cultural characteristics of the locale, assessing social control practices as reported by local professionals. Results confirm existence of CSEs in rural areas, which may produce negative outcomes and establish direct and indirect connections between young women and the justice system. Non-urban CSEs reveal origins common to those found in cities; patriarchy is identified as accounting for emergence of CSEs regardless of populous. The maintenance of such mechanisms, however, appear to be somewhat unique in rural communities; family name, a heavily-gendered veneer of idyllic but [un]safe milieux, and an absence of (and community reluctance to seek) vital services for abused girls and women are revealed as CSE characteristics in the areas of this study. Further, the current study challenges literature proclaiming solely positive results from high levels of collective efficacy, finding that strong collective efficacy in non-urban areas gathers close insider ties, but “outsiders,” which includes girls identified in this research, are defined quickly and deeply, placing them in significant peril. Policy recommendations include trauma-informed services in rural communities, coupled with education on characteristics associated with CSEs. While this research underscores over-incarceration of girls, it also suggests stop-gap approaches that address unique needs of young women in the justice system. Finally, recommendations for future CSE studies are offered.
Keywords: Coercive sexual environment; Gendered pathways; Juvenile justice; Rural criminology; Feminist methodology